Status of Solid Waste Recycling at Sholokbahar Ward in Chittagong, Bangladesh - Kabir, MH; Ismail, M; Jashimuddin, M (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted to analyze the solid waste recycling at Sholokbahar Ward of Chittagong City Corporation. Data were collected from primary waste collectors, i.e.Tokai, Feriwala, and Women waste collectors, waste dealers and different recycling plants through questionnaire survey and frequent field visits. The study found that the average amount of collected recyclable solid wastes was 121.37 kg/day in each solid waste recycling shop while waste picker was about 16 kg/day. Interestingly, the amount of average collected solid waste per day by Feriwala was significantly higher than Tokai and women waste pickers. Among of recyclable solid waste about 37% was scrap iron while only 16% was plastic bottle. The study also found that solid waste pickers generally collect wastes on foot while, among Feriwala only 23% use tricycle to collect wastes from door to door. We estimated that, by collecting recyclable solid wastes, each male and female waste picker earn, on an average, Tk. 80 and Tk.53 per day respectively. Finally, this study suggests that both governmental and non-governmental initiatives for solid waste recycling at Sholokbahar area can play a vital role to contribute our national economy, employment opportunities and environmental protection. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22078 J. Environ. Sci. & Natural Resources, 6(2): 07-11 2013